Controlling the oxidation and wettability of liquid metal via femtosecond laser for high-resolution flexible electronics - Zhang, Jingzhou; Zhang, Chengjun; Li, Haoyu; Cheng, Yang; Yang, Qing; Hou, Xun; Chen, Feng (Frontiers in Chemistry, 2022)
Liquid metal based electronic devices are attracting increasing attention owing to their excellent flexibility and high conductivity. However, a simple way to realize liquid metal electronics on a microscale without photolithography is still challenging. Here, the wettability and adhesion of liquid metal are controlled by combining stirring method, femtosecond laser microfabrication, and sacrificial layer assistant. The adhesive force of liquid metal is dramatically enhanced by adjusting its oxidation. The wetting area is limited to a micro-pattern by femtosecond laser and sacrificial layer. On this basis, a high-resolution liquid metal printing method is proposed. The printing resolution can be controlled even less than 50 μm. The resultant liquid metal pattern is applied for electronic skin, which shows uniformity, flexibility, and stability. It is anticipated that this liquid metal printing method will hold great promise in the fields of flexible electronics.